2018
DOI: 10.1159/000493284
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polysaccharide H-1-2 from Pseudostellaria Heterophylla Alleviates Type 2 Diabetes Mellitus

Abstract: Background/Aims: To investigate the potential therapeutic effect of novel polysaccharide H-1-2 from pseudostellaria heterophylla against type 2 Diabetes Mellitus (T2DM) and elucidate the underling molecular mechanisms. Methods: Relative expression of HIF1α and Sirt1 in T2DM patients was determined via real-time PCR. The direct binding of HIF1α on Sirt1 promoter was validated by ChIP assay. The inhibitory regulation of Sirt1 by HIF1α was analyzed using luciferase reporter assay. The endogenous protein of HIF1α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Some studies found that HIF-1α gene expression in T2DM patients with poor metabolic control was decreased [33]. However, some studies showed that the level of HIF-1α in T2DM patients was signi cantly higher than that in the control group, and insulin secretion increased when hypoxia was inhibited [34]. Therefore, the effect of HIF-1 signaling pathway on T2DM is not completely clear, which needs to be further con rmed.…”
Section: Component-target Molecule Docking Of Dhxdmentioning
confidence: 95%
“…Some studies found that HIF-1α gene expression in T2DM patients with poor metabolic control was decreased [33]. However, some studies showed that the level of HIF-1α in T2DM patients was signi cantly higher than that in the control group, and insulin secretion increased when hypoxia was inhibited [34]. Therefore, the effect of HIF-1 signaling pathway on T2DM is not completely clear, which needs to be further con rmed.…”
Section: Component-target Molecule Docking Of Dhxdmentioning
confidence: 95%
“…and Herba lycopi were shown to improve T2D in diabetic mice with nephropathy. 35,36 Cicada slough reduces IgA nephropathy, 37 an immune-mediated inflammatory condition of the glomerulus. 38 With its antiinflammatory and antioxidant effects and the capability to lower blood glucose and blood lipids by different mechanisms, the combination of components in this natural traditional Chinese remedy partially remedied disease-causing diabetic kidney injury in rats.…”
Section: Rat Kidney Histopathologymentioning
confidence: 99%
“…Notably, H-1-2 treatment also suppressed HIF1a protein levels (Figures 4B and 4D), confirming the previously reported anti-hypoxic property of H-1-2. 10,12 H-1-2 Downregulates AGR2 Expression through the Hypoxia-Responsive Element (HRE) in Its Promoter Region HIF1a was reported to promote AGR2 expression via the HRE from À937 to À912 bp on the AGR2 promoter sequence. 13 To experimentally interrogate the modulation of AGR2 expression by HIF1a, we constructed wild-type or mutated HRE-fused luciferase reporter plasmids (Figure 5A).…”
Section: H-1-2 Inhibits Agr2 and Hif1a In Pancreatic Cancermentioning
confidence: 99%
“…H-1-2, a novel homogeneous polysaccharide, was recently isolated from the polysaccharide fractions of the P. heterophylla extracts, 11 which was later shown to inhibit hypoxia in human pancreatic b cells. 12 These studies have prompted us to hypothesize that polysaccharide H-1-2 might exert the same anti-hypoxic activity in pancreatic cancer cells and suppress tumor progression. In addition, we sought to elucidate the downstream molecular mechanism responsible for the inhibitory effect of H-1-2 on pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%